Computer-Based Test (CBT) Assisted Assessment with Rasch Model to Improve Vocational High School Teachers' Skills - Novika Lestari; Erlin Eveline; M Akip; Julia Inayatul Marifah; Noperiska Fitri Ramda (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The aim of the community service program conducted is to enhance the skills of teachers and students at Bina Kusuma Private Vocational High School in Nanga Pinoh by using computer-based tests and improving teachers' skills in analysing the quality of assessment instruments using the Rasch model theory with the assistance of WinStep. The proposed solution to address these challenges involves conducting workshops and assisting in preparing test instruments. This includes guidance on using computer-based tests for both teachers and students, as well as workshops and assistance in applying the Rasch model to determine the validity of instruments. This community service used Participatory Action Research (PAR) method to find problems experienced by partners. The partners' issues consist of instruments from authentic assessments used at Bina Kusuma Private Vocational High School in Nanga Pinoh, which were made independently by the respective subject teachers and were directly used as benchmarks for student achievement, and the assessment instruments still did not utilise the available resources (computers and smartphones). Efforts made to address the partners' issues included developing authentic assessment instruments that were appropriate and valid. Based on the evaluation results of the activity implementation using the Kick Patrick Level 1 method, the average evaluation score for the presenters was 82.125, and the average evaluation score for the method, relevance and usefulness, facilities, and consumption was 88.75. The constraints encountered in this activity were that the community service program implementers needed to consider timing and conduct more in-depth evaluations. Recommendations for implementing community service program activities included developing a more structured community service program and integrating it with routine school activities.